Methodological Bases of Estimation of the Standard of Living of Population in the Regions of Ukraine Методологические основы оценки уровня жизни населения в регионах Украины - omelchenko Oksana. I. (Problemi Ekonomiki, 2010)
The methodological approach to estimation of a population’s living level in regions of Ukraine is offered in article. This approach is founded on calculation of a population’s living level as an integral factor by entropy method and on clustering regions of Ukraine on its basis. В статье предложен методологический подход к оценке уровня жизни населения в регионах Украины, который построен на расчете показателя уровня жизни населения, как интегрального методом энтропии, и кластеризации регионов на его основании.